Closure of anterior palatal fistula using tongue flap: our experience - Farooq Baba, Peerzada Umar; Ahmad, Tawheed; Mohsin, Mir; Zargar, Haroon Rashid; Wani, Adil Hafeez; Zaroo, Mohammad Inam; Bashir, Sheikh Adil; Rasool, Altaf; Bijli, Akram Hussain; Habib, Ovais; Masood, Muhsin; Yasir, Mir; et al. (International Journal of Research in Medical Sciences, 2016)
Background: Palatal fistula is one of the most common complications following cleft palate repair. It occurs mostly due to tip necrosis of palatal flaps. Small palatal fistulas are usually closed by transposition of adjacent tissues, however these local tissues are not sufficient for the closure of bigger fistulas. The tongue flap serves as a reliable and most easily obtainable local flap for closure of large sized palatal fistulas. Methods: This is a prospective study conducted from Aug 2006 to July 2015 in the department of Plastic & Reconstructive Surgery, SKIMS, Srinagar, Jammu Kashmir, India. A total of 25 patients with large anterior palatal fistula were treated using anteriorly based tongue flap. Patients were selected on the basis of size of fistula (> 1x1 cm), scarred local palatal tissue or history of fistula recurrence after previous attempts of closure using local palatal tissues. Results: In present study 25 patients of palatal fistula were treated using tongue flap. Eighty percent patients were in the age group of 3 to 5 years. Male-to-female ratio was 2:3. The largest dimension of treated fistula was 4x3 cm. There was partial dehiscence of flap suture line in two patients while remnant fistula was observed in three patients. None of our patients had flap necrosis. Conclusions: Tongue flap is an excellent and versatile option for closure of large palatal fistulas with high success rate and least morbidity.